DESIGN OF MULTIFUNCTIONAL MANUAL SCREEN PRINTING TOOL - Ludra Antara; Putu Darmawa; I Nyoman Gunung; Nyoman Sutarna (Logic : Jurnal Rancang Bangun dan Teknologi, 2024)
Screen printing is the simplest and most likely to be done manually. This printing technique is also an effective and efficient way in the development of small industries, the advantage of this screen printing business is that the capital is not too large, and also does not have to have special skills. The idea of redesigning a manual screen printing tool by combining 2 screen printing tools to get more effective and efficient results for screen printing operators. The advantages can perform precise printing results and can print several screen printing objects that before could only produce plastic screen printing only and after the addition of the design, the function of the tool will increase to be able to screen cups, cardboard, plastic bags, fabrics. Keywords: screen printing, stickers, cup molding, multifunction